The Data-Oriented Design Process for Game Development. (Computer (00189162), 2022)
Data-oriented design is a growing software development process for games that has not been well studied in academia. It seeks to subtract complicated design methods from problem solving and leverage the simplicity of what computer architecture is designed to do: input, transform, and output data.